Pandanus amaryllifoius Roxb. Leaves Ethanol Extract Ameliorates Lipid and Proinflammatory Cytokines Profiles in a Rat Model of Dyslipidemia - Martohap Parotua Lumbanraja; Kusnandar Anggadiredja; Neng Fisheri Kurniati; Hubbi Nashrullah Muhammad (Korean Pharmacopuncture Institute, 2024)
Objectives: Dyslipidemia has currently become a major health challenge that still opens for safer and more effective modes of treatment. The plant Pandanus amaryllifolius Roxb. (pandan) has been indicated to contain active ingredients that interfere with the pathological pathway of dyslipidemia. The aim of the study was to test the effects of pandan leaves ethanol extract on lipid and proinflammatory profiles in a rat dyslipidemic model. Methods: Dyslipidemia was induced by administration of high-fat feed for 8 weeks. Treatments (vehicle, the reference drug simvastatin at 1.8 mg/kg, and extract at 200, 300 or 600 mg/kg) were given for 4 weeks following the completion of induction. Results: Significant post-treatment decreases in total cholesterol, low density lipoprotein (LDL), and triglyceride levels in groups receiving all doses of extract and simvastatin were observed. Similar results were also found in regards to proinflammatory cytokines levels. Pandan extracts significantly lowered the concentrations of IL-6, TNF-α, and NFκB p65. Characterization of metabolite contents of the extract confirmed the presence of the previously suggested active alkaloids pandamarilactonine-A and B. Conclusion: Taken together, results of the present study implied the ameliorating effects of pandan leaves ethanol extract in dyslipidemic condition which is potential for opening an avenue in combating this essential component of metabolic disorder.